Clinical characteristics and outcome of very old (≥90 years) critically ill patients with need for intensive care after surgical intervention - Jöran Lücke; Jöran Lücke; Jöran Lücke; Franziska Stallbaum; Franziska Stallbaum; Franziska Stallbaum; Rikus Daniels; Pauline Theile; Jakob Izbicki; Anastasios D. Giannou; Anastasios D. Giannou; Anastasios D. Giannou; et al. (Frontiers in Medicine)
BackgroundDue to increasing life expectancy and decreasing morbidity, society is aging. Especially the group of very old patients (≥90 years) is currently increasing significantly. This leads to increasing numbers of very old patients requiring visceral and thoracic surgery. However, due to the multimorbidity of this cohort, postoperative intensive care is often required. Currently, insufficient data are available regarding the treatment and therapy of very old surgical critically ill patients. Therefore, this study aimed to investigate factors associated with early postoperative mortality to identify patients at risk.MethodsA retrospective cohort study was performed using clinical and sociodemographic data of all very old patients admitted to the Department of Intensive Care Medicine after visceral or thoracic surgery at the University Medical Center Hamburg-Eppendorf, between January 2008 and April 2019. Univariate comparisons and multivariate regression analysis were performed to identify factors associated with early postoperative death.ResultsIn total, 84 patients were included in the analysis. In this cohort, 27 (32.14%) died within 28 days after admission to the intensive care unit (ICU). Comparisons between these two groups show no association between the specifics of the operative procedure with early postoperative death. However, the living situation before hospital admission was shown to be significantly different between those patients who survived and those who died early after postoperative care. We further show an association of early postoperative death with preexisting cardiac diseases, increased creatinine levels, and high Simplified Acute Physiology Score II (SAPS II) upon admission to ICU.ConclusionThe SAPS II score and creatinine level upon admission could be identified as predictors of survival and may be beneficial for risk stratification in the critically ill patient cohort of the very old.